Elucidation of the binding mode of organic polysulfides on the human TRPA1 receptor - Nemes, Balázs; László, Szabolcs; Zsidó, Balázs Zoltán; Hetényi, Csaba; Feher, Adam; Papp, Ferenc; Varga, Zoltan; Szőke, Éva; Sándor, Zoltán; Pintér, Erika (Frontiers in Physiology, 2023)
Previous studies have established that endogenous inorganic polysulfides have significant biological actions activating the Transient Receptor Potential Ankyrin 1 (TRPA1) receptor. Organic polysulfides exert similar effects, but they are much more stable molecules, therefore these compounds are more suitable as drugs. In this study, we aimed to better understand the mechanism of action of organic polysulfides by identification of their binding site on the TRPA1 receptor. Polysulfides can readily interact with the thiol side chain of the cysteine residues of the protein. To investigate their role in the TRPA1 activation, we replaced several cysteine residues by alanine via site-directed mutagenesis. We searched for TRPA1 mutant variants with decreased or lost activating effect of the polysulfides, but with other functions remaining intact (such as the effects of non-electrophilic agonists and antagonists). The binding properties of the mutant receptors were analyzed by in silico molecular docking. Functional changes were tested by in vitro methods: calcium sensitive fluorescent flow cytometry, whole-cell patch-clamp and radioactive calcium-45 liquid scintillation counting. The results show that the cysteines forming the conventional binding site of electrophilic agonists, namely C621, C641 and C665 also bind the organic polysulfides, with the key role of C621. However, only their combined mutation abolished completely the organic polysulfide-induced activation of the receptor. Since previous papers provided evidence that organic polysulfides exert analgesic and anti-inflammatory actions in different in vivo animal models, we anticipate that the development of TRPA1-targeted, organic polysulfide-based drugs will be promoted by this identification of the binding site.